O esporte e a economia criativa - Grael, Nicholas Pellicano (2024)
The main goal of this project was to analyze how sports are related to creative economy. In order to achieve this goal, the central argument, initially developed, was that sports, given its current creative characteristics, are directly related to the concepts of creative economy and can even be recognized as a creative segment. The project has four chapters of review of literature, arising from the specific objectives, and each chapter addresses a different aspect chosen by the researcher to relate sports and creative economy. The first chapter deals specifically with the creative economy, and what defines an activity of the creative industry, in addition, it has a section dedicated to raising evidence of the presence of creativity within sports. The second chapter explains the aestheticization process that society has been going through, and how it reflects on the world of sports, according to the concepts of Lipovetsky and Serroy. The third chapter discusses how sports are used as an instrument of soft power, explaining what soft power is, and its relationship with creative economy. The last chapter talks about the experience economy and its beneficial relationship with sports and sporting events. An exploratory and descriptive research was carried out, through a bibliographical survey that aimed for information throughout the review of literature, and through a qualitative field research, with semi-structured interviews. After this, the secondary data collected was crossed with the primary data from the interviews, to conclude that the central argument was partially corroborated and that sports are directly related to the creative economy, however with some reservations about being considered a creative segment